Pencapaian Kemandirian Operasional Melalui Pengelolaan Aset Di Pondok Pesantren Annuqayah - Rendri Pratama Wahyu Priandhika; Muhammad Nafik H.R (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
Boarding school is currently experiencing rapid development. this can be evidenced by the increasing number of boarding schools each year are offset by the growing number of students. The method used is qualitative approach with the strategy case study. The collection of data that is passed is the interview to the informan, the leader of Islamic boarding school, the leader of foundation, chairman of the cooperative Islamic boarding school, as well as the collection of secondary data derived from the documents relating to asset management of Annuqayah Islamic boarding school. Research purposes to determine capital asset management in operational independence. The analysis technique used is the technique of manufacture of explanation with narrating the interviews with informants. Results from this study is optimally manage assets can make Annuqayah Islamic boarding school financially independent. Revenues that received from manage assets can assist in building new facilities which has been using grants.